PERANCANGAN PORTAL DIGITAL DAN MIRROR SYSTEM FAKULTAS TEKNIK UNIVERSITAS TANJUNGPURA - Sandra, Mel (Jurusan Informatika Universitas Tanjungpura, 2014)
Abstract - The information portal is one ofthe media in generating information topeople around the world. This theinformation portal is also implemented inthe Faculty of Engineering, University ofTanjungpura in order to fulfill theinformation needs of its academiccommunity. Various types of informationsystems that owned by the Faculty ofEngineering, University of Tanjungpurabecome a reason why this portal is verynecessary as a campus informationcenter. The media that used to inform theinformation would be better if it providestwo-way communication facilities so thatthe result of the information is not only ofby the managers but also of the public,especially the academic community of theFaculty of Engineering, UniversityTanjungpura. Email is one of the two-waycommunication media and this featurecan also be applied in the informationportal designed for web-based similarity.The amount of resources that requiredthe information needs to be maintained, itis becoming a basic necessity of a mirrorsystem that can be used to anticipateinterference with the resources so that theinformation can still be used even ifresources are experiencing interference.Keywords: the information portal, mirrorsystems, mail service, e-mail.